The Waiting Room Hypothesis revisited by orchids: were orchid mycorrhizal fungi recruited among root endophytes? - Selosse, Marc-André; Petrolli, Rémi; Mujica, María Isabel; Laurent, Liam; Perez-Lamarque, Benoît; Figura, Tomáš; Bourceret, Amelia; Jacquemyn, Hans; Li, Taiqiang; Gao, Jiangyun; Minasiewicz, Julita; Martos, Florent (Annals of botany, 2022)
BACKGROUND: As in most land plants, the roots of orchids (Orchidaceae) associate with soil fungi. Recent studies have highlighted the diversity of the fungal partners involved, mostly within Basidiomycotas. The association with a polyphyletic group of fungi collectively called rhizoctonias (Ceratobasidiaceae, Tulasnellaceae and Serendipitaceae) is the most frequent. Yet, several orchid species target other fungal taxa that differ from rhizoctonias by their phylogenetic position and/or ecological traits related to their nutrition out of the orchid roots (e.g. soil saprobic or ectomycorrhizal fungi). We offer an evolutionary framework for these symbiotic associations. SCOPE: Our view is based on the 'Waiting Room Hypothesis', an evolutionary scenario stating that mycorrhizal fungi of land flora were recruited from ancestors that initially colonized roots as endophytes. Endophytes biotrophically colonize tissues in a diffuse way, contrasting with mycorrhizae by the absence of morphological differentiation and of contribution to the plant's nutrition. The association with rhizoctonias is probably the ancestral symbiosis that persists in most extant orchids, while during orchid evolution numerous secondary transitions occurred to other fungal taxa. We suggest that both the rhizoctonia partners and the secondarily acquired ones are from fungal taxa that have broad endophytic ability, as exemplified in non-orchid roots. We review evidence that endophytism in non-orchid plants is the current ecology of many rhizoctonias, which suggests that their ancestors may have been endophytic in orchid ancestors. This also applies to the non-rhizoctonia fungi that were secondarily recruited by several orchid lineages as mycorrhizal partners. Indeed, from our review of the published literature, they are often detected, probably as endophytes, in extant rhizoctonia-associated orchids. CONCLUSION: The orchid family offers one of the best documented examples of the 'Waiting Room Hypothesis': their mycorrhizal symbioses support the idea that extant mycorrhizal fungi have been recruited among endophytic fungi that colonized orchid ancestors.
Keywords: symbióza; Mycorrhizae; endophytism; rhizoctonias; Phylogeny; endofyty; saprobic fungi; mycoheterotrophy; Symbiosis; Ectomycorrhizal fungi; Waiting Rooms; mixotrophy; mykorhiza; Orchidaceae; fylogeneze; čekárny; Endophytes